Analisis Penggunaan Media Spelling Puzzle untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Disleksia di Sekolah Dasar Penyelenggara Pendidikan Inklusi - Ina Agustin; Ifa Seftia Rakhma Widiyanti (Universitas PGRI Semarang, 2022)
Children with special needs require educational services in the form of a different learning process from children in general. One kind of child with special needs is a dyslexic child. In general, dyslexic children experience several learning difficulties, one of which is difficulty reading and writing. This study aims to analyze the use of spelling puzzle media in improving the reading ability of dyslexic children. The subjects in this study were dyslexic grade III students at SDN Tambakboyo II who collected four students. The method used in this research is descriptive qualitative. Data was collected through interviews, reading tests and observations. Data is presented in the form of diagrams and then analyzed descriptively. The main problem in this study is whether the spelling puzzle media can help dyslexic children improve reading skills. The results showed that the use of spelling puzzle media can improve reading skills at the beginning reading level. Increased reading ability as a reaction to the increase in memory and motivation of dyslexic children through spelling puzzle pieces. Other findings in this study increased learning activities, motivation and interest in reading dyslexia.